(untitled) (Al-Academy, 2016)
Designing cloth is a part from culture and civilization of the area of every state to prove its being in all times because it is grown with Man to establish both goals: usefulness and beauty.It is necessary that designer puts in his mind the importance of the designing sources that he derives his designs from , because those sources are also important in that time especially :The Iraqi Ancient Civilization , the Islamic Civilization and Iraqi Folklores . Not to use the cloth sources that doesn’t have well known roots in addition to lacking of elements and bases of balance in its different aspects. In conclusion to that studying research subject comes. (Balance Role in designing cloth curtains) The idea or the problem of the research is the designs of the cloth curtain lack balance element thought the design elements and bases of design unit. Or through the repletion of this design unit on cloth also those designs don’t have the feature of Iraq but foreign from aspects feature of view.This research aims to reveal the reality of designing cloth curtain in Baghdad factories and recruiting balance in designing cloth curtain in according to the needs of designing cloth both usefulness and beauty from Iraqi roots like the Iraqi and Islamic ancient civilization this is the first chapter.The second chapter consist theoretical sides, balance its types, unit and balance in designing cloth curtain, association and perfect ness, the relationship of with elements and basis of designing in cloth curtain , the relationship of balance with the system of designing curtain and at last the subject of designing of cloth curtain .The third chapter deals with research procedures which consist research approach which is descriptive and analytical and contains (19) design samples of cloth curtain. (9) Samples are chosen to represent subject sample studying and excluding (10) samples for reasons. So samples are chosen deliberately. The research tool is a form of analysis of samples. The following results show in chapter four:1-Central balance comes first, then not central and illusion at last radiant.2-Lines organization first then beam and net at last the central.The quadrilateral repetition comes first role than triple repetition or dropping.3-The use of full rhythm then alternately and finally the free. The subject of designing and the way of exclusion altered plants comes first then altered animals, human and geometrical at last geometrical plants,4-The designer recruits contradicting color then harmonic and contradicting ones then harmonic ones and at the end neutral.Then suggested designing nine (9) samples were recruited for designing curtain cloth. The aspect of recruiting as follow:1-The Iraqi, Islamic civilization and folklores are the great source for designs without deforming them and if they reduced should kept genuine. 2- Nature is important source to inspire from. 3- Alter conceder (altering shapes, derived objects) is the successful designer work as altering leave shapes to toys figure and altering Baghdadi shanasheel from its known shape to non objective then recruiting it in a form of modern Iraqi cultural way to become curtain design